OPTIMASI DOSIS ALOKSAN UNTUK INDUKSI DIABETES MENGGUNAKAN HEWAN MODEL TIKUS PUTIH BETINA - Nur Qomariyah 1, ; Mulyati Sarto2, (Matematika dan Sains, 2011)
Alloxan was one diabetogen often used to study diabetes either with single or repeated doses. Single dose used for induction of diabetic rats ranged 100-180 mg/kgbw, but the results are often not satisfied or not maximum, the success rate, mortality, and duration of diabetic conditions in experimental animals. The purpose of this study to determine the dose of alloxan for induction of diabetic which lasted more than 3 weeks. The research was done with complete randomized design using female white rats, Wistar strain, age 4 months, weight 170-200 grams for 20 days. Thirty-five rats were divided into seven groups, were 5 of each. All test animals induced with aloksan monohydrate in a dose respectively 100, 110, 120, 130, 140, 150, and 160 mg/kgbw intraperitonially. The results were analyzed ANAVA and LSD (p <0.05). The results for 20 days showed dose alloxan of 100 and 110 mg / kgbw could not produce a diabetic condition, dose of 120 mg/ kgbw can induce diabetic but did not survive more than 7 days, the dose can induce diabetic 130mg/kgbw which last up to 20 days. Doses of 140, 150, and 160mg/kgBB can induce diabetic, but have high mortality rate of between 60-80%. Therefore, dose of alloxan 130 mg/kgbw most effective for the induction of diabetic and last up to 20 days and potentially more than 20 days.